Care for the sick in ancient monasteries in the light of selected monastic rules - Kołosowski, Tadeusz (Saeculum Christianum. Pismo Historyczne, 2021)
This article attempts to answer the question of how Eastern and Western monastic rules provided for the sick in ancient monasteries. Did they enjoy any kind of special status among their brothers or sisters? Who was responsible for the sick in the monastery and how they took care of the ill? In this regard, monastic rules are an interesting and unique source of information about activities undertaken to care for ill members of the monastic community. We identified and analysed seven monastic rules. These rules were written in different regions of the contemporary world: Egypt, North Africa, Gaul, Italy, and Spain. One was written in the 4th, and the other in the 7th century, and both concern monks and consecrated women. Each rule appoints some individuals responsible for the care of the sick. These were usually nurses and monastic dispensers. Some rules determined the required personality traits. The general supervision over the care of the sick was entrusted to the monastery superior. Separate rooms or cells were designated for the sick, sometimes together with a dining room, pantry, or kitchen. All the rules seek to ease the requirements concerning the consumption of meals, fasts, and hygiene for the sick. If capable, they should engage in lighter works.